A wheel–rail normal contact model using the combination of virtual penetration method and strip-like Boussinesq's integral. Issue 6 (3rd June 2023) - An, Boyang; Wang, Ping
Abstract : This paper reports a new non-Hertz normal contact model for the engineering computations such as vehicle-track dynamics and wheel-rail damage prediction. The model is developed as a combination of virtual penetration method and Boussinesq's integral. A first novel aspect is the proposed virtual penetration method to compensate the inconsistence introduced by this combination, (i) a 'stepwise penetration scaling coefficient' approach that adapts to the lateral contact boundary is presented; (ii) we propose a new formula for the longitudinal contact boundary to compensate the error introduced by the step-by-step increase of interpolated penetration. A second novelty is the use of strip-like Boussinesq's integral for strip discretized contact patch to achieve the fast computation. On the one hand, it makes this model easier to convergence since it only considers the result in the center of each strip. On the other hand, we propose a fast method of generating influence coefficient matrix. Some numerical tests are evaluated by the CONTACT software and compared with KP method and STRIPES. In addition, the comparison of modeling approach and computational cost are discussed in detail.